Pemetaan Dan Peningkatan Mutu Pendidikan Pada SMP Bilingual Terpadu Junwangi Krian Sidoarjo - Hasyim Asyari (Institut Agama Islam Negeri Purwokerto, 2019)
The quality of education is a standard that must be maintained by educational institutions in Indonesia. Quality assurance of school is an education management business in maintaining the process of determining and fulfilling management quality standards on an ongoing basis so that producer consumers and other interested parties obtain satisfaction. The implementation of quality assurance, it is hoped that it will be able to create quality graduates. The quality assurance standards have been stipulated in Government Regulation Number 19 of 2005. SMP Bilingual Terpadu is an educational institution that has applied the education quality assurance system. In each semester, school managers try to map and improve the quality of schools. Improving the quality of education in SMP Bilingual Terpadu based on standard mapping results. The results of the mapping will be used as a basis for increasing the implementation and supervision of quality assurance at SMP Bilingual Terpadu Krian Sidoarjo.